Transforming the medical library into a welcoming learning space: a collaborative project (Journal of EAHIL, 2020)
The University of Bern is expanding the training of future physicians. This significant increase in the number of medical students has led to a shortage of student study places in the medical library “Fachbereichsbibliothek Bühlplatz” (FBB) of the University Library of Bern. For this reason, during the summer of 2019, the FBB was refurbished and reopened a under a new name: Bibliothek Medizin providing more library services and student study places.